Learning Self-Regulation Questionnaire (SRQ-L): Psychometric and Measurement Invariance Evidence in Peruvian Undergraduate Students - Merino-Soto, César; Chávez-Ventura, Gina; López-Fernández, Verónica; Chans, Guillermo M.; Toledano-Toledano, Filiberto (Sustainability (Switzerland), 2023)
Given the theoretical and applied importance of self-regulation in learning, our study aimed to report the internal structure of the psychometric properties of the Learning Self-Regulation Questionnaire. Five hundred and ninety-six Peruvian university students participated in their first to tenth semesters on campuses in Lima, Trujillo, and Cajamarca. Nonparametric scalability, dimensionality, reliability (score and item levels), and latent invariance were analyzed. The results showed that reducing the number of response options was necessary. Reducing the number of items also produced better scaling. Two slightly related dimensions were strong internal validity and acceptable item reliability; furthermore, reliability was adequate. Age and gender had trivial correlations in item variability. Finally, differences between the semesters were obtained in the means, variances, and latent correlations. In conclusion, we propose a better definition of the constructs of autonomy and control measured by the SRQ-L. This article also discusses the limitations and implications of the study.
Keywords: educational innovation; higher education; invariance; learning; professional education; self-regulation; social cognition; validity; Scopus; JCR